Processus de mise en œuvre de la réforme des études en masso-kinésithérapie par une équipe de direction : entre traduction, dynamiques d'innovation et enrôlement des formateurs - Thérèse Perez-Roux; Éric Maleyrot (Nantes Université, 2020)
Over the last ten years in France, in the field of health, the paramedical professions have all undergone a reform of their studies involving a reengineering of training. This contribution presents a qualitative study that aims to uncover the implementing process of the studies in masso-physiotherapy reform (2015), by a management team, within a training institute. The reengineering operated by this management is studied over the first four years post-reform (2015-2019). The process analysis is carried out using a conceptual framework that takes into account the challenges of professionalisation and the training schemes, chosen in an innovating dynamic. In addition, leadership phenomena are discussed. The results show a complex process. For the management, it is first of all a matter of designing new reflexive schemes and then engaging the trainers in the expected approaches. The leadership developed reveals gaps and changes generated by such a project. A number of tensions linked to the trainers' reform understanding are thus identified. Finally, the results indicate the extent to which the management puts new work projects into perspective, in an innovating and prospecting process that requires both stakeholders' understanding and involvement.